Pemberdayaan Peternak KTT Jaya dan KTT MBS di Desa Purworejo Melalui Pelatihan Pembuatan Complete Feed Pengabdian Program Desa Binaan - Joko Riyanto; Ayu Intan Sari; Aidila Kanaya Putri; Abelita Kusbianto; Aisah Nurul Aulia Rahma; Sesilia Novita Ardelie; Muhammad Fahturrohman Zuhdi; Okid Parama Astirin; Syamsul Hadi; Ari Prasetyo; Zakaria Husein Abdurrahman (Universitas Sebelas Maret, 2025)
Empowerment of Jaya Farmer Group and MBS Farmers in Purworejo Sragen Through Complete Feed Preparation Training for the Village Development Program. The Village Empowerment Program implemented in Purworejo Village, Gemolong District, Sragen Regency, was motivated by the community's interest in raising dairy goats. The dairy goats that are quite developed include PE, Jawa Randu, and Sapera dairy goats. This Village Development Program is funded by the Ministry of Education, Culture, Research, and Technology. The development of dairy goats starts from the smallest unit, namely farmers, by forming a Livestock Farmers Group association. The Village Empowerment Program invites two Livestock Farmers Groups in Purworejo Village to become partners. The Livestock Farmers Groups targeted in the village empowerment activities are the Jaya Livestock Farmers Group and the Muda Bakti Sejahtera Livestock Farmers Group. The problems that arise in livestock farmers are related to milk production that is not yet optimal. Low milk production can be caused by the provision of feed that is not Accordance with the nutritional needs of livestock. The nutritional needs of livestock in each physiological phase are different. The solution provided through this Village Empowerment Program is the manufacture of complete feed for dairy goats. Complete feed is a fairly simple technology in livestock feed management. The ration for making complete feed is adjusted by looking at the availability of feed ingredients around Purworejo Village, namely cassava, bran, corn cobs, CGF, copra cake, and minerals. The Village Empowerment Program begins with socialization followed by workshops and mentoring. The conclusion after a series of programs have been completed is that farmers can understand the use and process of making complete feed technology which is assessed through the tests provided and their activeness during the mentoring session.